Fluorescence intensity of parathyroid glands in thyroid and parathyroid surgery: a near-infrared autofluorescence study - Yu, Fan; Yi, Xiaolei; Lin, Zihan; Wu, Yinyue; Luo, Quanyong; Wu, Bo (Frontiers in Surgery, 2025)
ObjectiveNear-infrared autofluorescence (NIRAF) imaging shows promise in identifying parathyroid gland (PG) during surgery. However, the clinical application of NIRAF faces challenges due to the heterogeneous fluorescence intensity (FI) of PGs observed in different thyroid and parathyroid diseases. This study aimed to evaluate the effectiveness of NIRAF in PG detection and to analyze the FI of PGs in patients with various thyroid and parathyroid diseases.MethodsA total of 105 patients undergoing thyroidectomy and parathyroidectomy were enrolled. Intraoperative NIRAF imaging was used to detect PGs, and the FI values were quantified using ImageJ software. Normal PGs were grouped according to the pathological results of ipsilateral thyroid diseases. Compare and analyze the FI values of normal and diseased PGs.ResultsA total of 239 PGs were detected during surgery. 225 PGs were identified by NIRAF. The NIRAF identification rate was significantly higher than visual identification (94.1% vs. 81.2%, p < 0.001). NIRAF demonstrated high performance in PG identification, with sensitivity, specificity, and positive predictive values and negative predictive values to predict PGs were 95.4%, 77.5%, 90.5% and 88.1%, respectively. The FI of PGs was higher in patients with papillary thyroid carcinoma (1.39 ± 0.21), follicular nodules of thyroid (1.45 ± 0.25), nodular thyroid gland (1.36 ± 0.19) than in those with hyperthyroidism (1.06 ± 0.28) and primary hyperparathyroidism (1.17 ± 0.23). Superior PGs in Stage I exhibited higher FI compared to PGs in Stage II (p = 0.025). In Stage II, the FI of inferior PGs was significantly higher than that of superior PGs (p < 0.001). The FI of PGs in both Stage I and II was significantly higher than in Stage III.ConclusionsNIRAF demonstrates high efficiency in identifying PGs across various surgical stages, outperforming conventional visual identification. The FI of superior and inferior PGs exhibits significant variability across different intraoperative stages. Surgeons should exercise caution when identifying PGs in patients with primary hyperparathyroidism and hyperthyroidism, as these conditions are associated with lower FI compared to other thyroid diseases.